Option D:
is the function
Explanation:
Let the general form of quadratic equation be ![$y=a x^{2}+b x+c$](https://tex.z-dn.net/?f=%24y%3Da%20x%5E%7B2%7D%2Bb%20x%2Bc%24)
The function passes through the intercepts
and
and also passes though the point ![$(-1,10)$](https://tex.z-dn.net/?f=%24%28-1%2C10%29%24)
Substituting the points
,
and
in the equation
, we get,
-----------(1)
----------(2)
-----------(3)
Subtracting (1) and (2), we get,
-----------(4)
Subtracting (2) and (3), we get,
------------(5)
Multiplying equation (4) by 5 and equation (5) by 4, to cancel the term b when adding, we get,
![-60a-30b=0\\\ 90a+30b=-60\\--------\\30a=-60\\\ \ a=-2](https://tex.z-dn.net/?f=-60a-30b%3D0%5C%5C%5C%2090a%2B30b%3D-60%5C%5C--------%5C%5C30a%3D-60%5C%5C%5C%20%5C%20a%3D-2)
Thus, the value of a is ![a=-2](https://tex.z-dn.net/?f=a%3D-2)
Substituting
in equation (4), we get,
![$\begin{aligned}-12 a+6 b &=0 \\-12(-2)-6 b &=0 \\ 24-6 b &=0 \\ 24 &=6 b \\ 4 &=b \end{aligned}$](https://tex.z-dn.net/?f=%24%5Cbegin%7Baligned%7D-12%20a%2B6%20b%20%26%3D0%20%5C%5C-12%28-2%29-6%20b%20%26%3D0%20%5C%5C%2024-6%20b%20%26%3D0%20%5C%5C%2024%20%26%3D6%20b%20%5C%5C%204%20%26%3Db%20%5Cend%7Baligned%7D%24)
Thus, the value of b is ![b=4](https://tex.z-dn.net/?f=b%3D4)
Now, substituting the value of a and b in equation (1), we have,
![$\begin{aligned} 4 a-2 b+c &=0 \\ 4(-2)-2(4)+c &=0 \\-8-8+c &=0 \\ c &=16 \end{aligned}$](https://tex.z-dn.net/?f=%24%5Cbegin%7Baligned%7D%204%20a-2%20b%2Bc%20%26%3D0%20%5C%5C%204%28-2%29-2%284%29%2Bc%20%26%3D0%20%5C%5C-8-8%2Bc%20%26%3D0%20%5C%5C%20c%20%26%3D16%20%5Cend%7Baligned%7D%24)
Thus, the value of c is ![c=16](https://tex.z-dn.net/?f=c%3D16)
Now, substituting the value of a,b and c in the general formula
, we get,
![y=-2x^{2} +4x+16](https://tex.z-dn.net/?f=y%3D-2x%5E%7B2%7D%20%2B4x%2B16)
Taking out the common term as -2 we get,
![y=-2(x^{2} -2x-8)](https://tex.z-dn.net/?f=y%3D-2%28x%5E%7B2%7D%20-2x-8%29)
Factoring , we get,
![$y=-2(x+2)(x-4)$](https://tex.z-dn.net/?f=%24y%3D-2%28x%2B2%29%28x-4%29%24)
Thus, the function is ![$f(x)=-2(x+2)(x-4)$](https://tex.z-dn.net/?f=%24f%28x%29%3D-2%28x%2B2%29%28x-4%29%24)